PEMANFAATAN MEDIA INTERAKTIF DALAM MENINGKATKAN KETERLIBATAN BELAJAR ANAK USIA DINI PADA PEMBELAJARAN BAHASA INGGRIS - Sry Wahyuni; Ita Sarmita Samad (Jurnal Prasasti Ilmu, 2026)
This study aimed to explore the use of interactive learning media in enhancing young learners’ engagement in English language learning. The study employed a qualitative approach, with data collected through classroom observations and interviews with teachers at PAUD Insan Masagena, Makassar. The findings revealed that the use of interactive media, such as educational games, picture cards, concrete objects, audio-visual media, and interactive quizzes, was able to increase students’ active participation, attention, and enthusiasm during the learning process. Singing activities combined with music and movement also helped build learning readiness and create a more enjoyable classroom atmosphere. In addition, the use of translanguaging and repetitive instructions assisted students in gradually understanding English vocabulary and classroom instructions through the association between language and concrete activities. The findings indicate that young learners’ engagement is strongly influenced by how teachers design interactive, enjoyable, and developmentally appropriate learning experiences. Therefore, the use of interactive media and adaptive communication strategies plays an important role in creating more effective and meaningful English learning for young learners.